2022
DOI: 10.1029/2021gl096173
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Observations of the Impact of Individual Aircraft on Ice Crystal Number in Thin Cirrus Clouds

Abstract: Contrails can persist in cloud‐free supersaturated air, increasing high‐cloud cover, and inside natural cirrus cloud, modifying the microphysical properties of them. The latter effect is almost unknown, partly because of the lack of height‐resolved measurements and the capability of measurements to penetrate inside the cloud. New retrievals of the ice crystal number concentration from combined satellite cloud radar and lidar measurements (CloudSat/CALIPSO; DARDAR‐Nice algorithm) now allow for satellite‐based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…We apply multiplication factors of 0.1, 0.5, 0.9, 1.1, 1.25, 1.5, 2 and 10 to explore a wide range of possible aviation perturbations. The ICNC×1.25, ×1.5 experiments are closest to the satellite-based estimates of Marjani et al (2022), while the ICNC×0.5 and ×2 experiments represent large but still-plausible perturbations. The ICNC×0.1 and ×10 perturbations are unrealistic, but useful to study the degree of linearity in ice water response.…”
Section: Idealised Perturbationsmentioning
confidence: 64%
See 2 more Smart Citations
“…We apply multiplication factors of 0.1, 0.5, 0.9, 1.1, 1.25, 1.5, 2 and 10 to explore a wide range of possible aviation perturbations. The ICNC×1.25, ×1.5 experiments are closest to the satellite-based estimates of Marjani et al (2022), while the ICNC×0.5 and ×2 experiments represent large but still-plausible perturbations. The ICNC×0.1 and ×10 perturbations are unrealistic, but useful to study the degree of linearity in ice water response.…”
Section: Idealised Perturbationsmentioning
confidence: 64%
“…The perturbations induced are intended to be plausible. For example, we apply ICNC perturbations of 25% and 50%, which are comparable to the results of Marjani et al (2022).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Using the advected flightpaths to identify potential aircraft-modified clouds (e.g. Tesche et al 2016, Duda et al 2019, Marjani et al 2022, Chevallier et al 2023 avoids the requirement for tracking COs and potential selection biases associated with the filtering and tracking processes. Although the CNN produces a considerable number of false positives (figure 3(a)), these are significantly reduced over the ocean.…”
Section: Fleet-wide Contrailsmentioning
confidence: 99%
“…Following the same methodology, Marjani et al (2022) focused on the number concentration and found an increase within a few hundred meters behind the aircraft and below its flight track. In line with airborne observations, Verma and Burkhardt (2022) simulated contrail formation within pre-existing cirrus and found that contrails increased the ice crystal number concentration of cirrus by a few orders of magnitude.…”
mentioning
confidence: 99%